At the borders of medical reasoning: aetiological and ontological challenges of medically unexplained symptoms - Eriksen, Thor Eirik; Kerry, Roger; Mumford, Stephen; Lie, Svein Anders Noer; Anjum, Rani Lill (BioMed Central, 2013)
Medically unexplained symptoms (MUS) remain recalcitrant to the medical profession, proving less suitable for homogenic treatment with respect to their aetiology, taxonomy and diagnosis. While the majority of existing medical research methods are designed for large scale population data and sufficiently homogenous groups, MUS are characterised by their heterogenic and complex nature. As a result, MUS seem to resist medical scrutiny in a way that other conditions do not. This paper approaches the problem of MUS from a philosophical point of view. The aim is to first consider the epistemological problem of MUS in a wider ontological and phenomenological context, particularly in relation to causation. Second, the paper links current medical practice to certain ontological assumptions. Finally, the outlines of an alternative ontology of causation are offered which place characteristic features of MUS, such as genuine complexity, context-sensitivity, holism and medical uniqueness at the centre of any causal set-up, and not only for MUS. This alternative ontology provides a framework in which to better understand complex medical conditions in relation to both their nature and their associated research activity.